1999
DOI: 10.1046/j.1365-2222.1999.00612.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy to bovine β‐lactoglobulin: specificity of human IgE to tryptic peptides

Abstract: Three peptides were identified as major epitopes, recognized by a large majority of human IgE antibodies. Numerous other epitopes are scattered all along the Blg sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
139
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 206 publications
(163 citation statements)
references
References 14 publications
14
139
0
1
Order By: Relevance
“…24) In pevious studies β-lg allergy was generally considered to be a Th2-dominant chronic inflammatory disease. 25) In our study, increased Th2-cytokine, IgE levels and eosinophils are observed. Recent studies on non-Th1/Th2-cell-based mechanisms for the pathogenesis of allergic diseases identified two additional Th cell subsets, Th17 cells and Treg cells.…”
Section: Discussionsupporting
confidence: 63%
“…24) In pevious studies β-lg allergy was generally considered to be a Th2-dominant chronic inflammatory disease. 25) In our study, increased Th2-cytokine, IgE levels and eosinophils are observed. Recent studies on non-Th1/Th2-cell-based mechanisms for the pathogenesis of allergic diseases identified two additional Th cell subsets, Th17 cells and Treg cells.…”
Section: Discussionsupporting
confidence: 63%
“…The site of substitution for BLG coding sequences was thus adequate, since PrtB-BLG and PrtB-T6 were properly processed by the L. lactis secretion machinery and escaped intracellular proteolysis. Anti-BLG antiserum was not reactive, in both ELISA and immunoblot analysis, to T6-expressing clones, confirming previous reports of the low level of antigenicity of this BLG peptide (22,28). The fact that anti-T6 antiserum, which recognizes native BLG in ELISA, failed to react with recombinant L. lactis expressing full-length BLG might reflect either epitope masking or subtle conformational changes in the fusion protein.…”
Section: Discussionsupporting
confidence: 84%
“…For example, ovomucoid [1] from the egg white, M fraction from fish [2] and beta lactoglobulin [3] from cow's milk have maximum antigenicity comparatively with other antigens from the same foods.…”
mentioning
confidence: 99%